Conocimientos y actitud hacia el tratamiento en pacientes con tuberculosis pulmonar del Hospital Distrital Santa Isabel. El Porvenir - Saavedra Gutierrez, Melissa Clotilde (2019)
The present study, correlational descriptive cross-sectional, whose objective was to determine the relation between the knowledge and attitudes towards the treatment among pulmonary tuberculosis patients in Santa Isabel district hospital. El Porvenir. The sample universe was formed by 17 patients attended in the ESNPCT in this hospital. To collect data two instruments were used: A survey and a questionnaire created by Huaynates (2006), which was developed based on “Doctrine Update, Rules and Procedures for the Tuberculosis control programme in Peru” (MINSA, 2011), and adapted by Saavedra (2018), based on the Health Standards for the Tuberculosis Control (NTSTBC, 2006), statistical analyses were performed using the Chi Square Test, the results show that 52.9 percent of patients have a medium level of knowledge, 47.06 percent have a high level. Also the findings show that 76.47 percent have demonstrated a good attitude, and 23.53 percent show Indifference. There is therefore a statistically significant relationship between both variables ( = 0.05).